The Mental Health of High School Students During the COVID-19 Pandemic - Rao, Maya E.; Rao, Dhananjai M. (Frontiers in Education, 2021)
The American Psychological Association (APA) reports 81% of Gen Z teens (ages 13¬–17) have experienced more intense stress during the COVID-19 pandemic. This study uses a survey-based approach along with robust statistical analyses to identify key stressors from a set of students in a high school in Midwest USA. Our survey includes a broad range of stressors (15 explanatory variables) specific to high schoolers, controls (4 factors for pre-existing conditions), and mental health estimators (7 dependent variables) to identify changes in mental wellbeing during the pandemic. The results (n = 107) show good consistency in our estimators (Cronbach’s ɑ=0.78) and statistically significant (t=0.636, p ≪ 0.001) degradation in the mental health. Correlation (r=0.2, p=0.034) and regression analysis showed that online learning (β1=-0.96, p=0.004) has the most influence on degradation in mental health, with some race-based differences. Exercise time helps reduce mental health degradation (β3=-0.153, p=0.037). Many other factors such as gender, homework time, school time, pre-existing mental health issues, and therapy did not have a significant influence on mental health degradation. Analysis of freeform feedback identified the following three recurring themes: increased stress due homework (13.2%), social isolation or lack of social interactions (8.5%), and lack of support for mental wellbeing (12.3%).